Mary Jane$1 (BHer Visits - Judson, Clara Ingram, 1879-1960; White, Frances (Salt Lake City, UT : Project Gutenberg, 2005)
"Mary Jane$1 (BHer Visit" by Clara Ingram Judson is a children$1 (Bs novel written in the early 20th century. The story centers around a spirited five-year-old girl named Mary Jane who embarks on a delightful trip to visit her grandparents in the countryside. Throughout her visit, she explores the new environment, interacts with various farm animals, and engages in wholesome activities that reflect the warmth and charm of rural life. The opening portion of the book introduces Mary Jane as she awakens on a train, filled with excitement for her journey to Glenville to see her Great-Grandmother. Upon arrival, she is greeted by her Grandfather, and with eager curiosity, she begins to explore her new surroundings. The narrative captures Mary Jane's initial feelings of wonder and trepidation, particularly as she encounters a pig that initially frightens her, only to be comforted by her Grandfather. The chapter showcases Mary Jane's adventurous spirit through her playful interactions, from putting on her shoes to eagerly anticipating the adventures ahead on the farm, setting the stage for the enchanting experiences she will encounter during her visit. (This is an automatically generated summary.)s
Release date is 2005-05-31
E-text prepared by Al Haines
Keywords: Girls -- Juvenile fiction; Country life -- Juvenile fiction; Grandparents -- Juvenile fiction